Factor structure and predictors of causal beliefs about seven mental illnesses among the Singapore general population - Tan, Yoke Boon; Tay, Eng Hong; Shahwan, Shazana; Gunasekaran, Savita; Lim, Benedict Wei Zhi; Tan, Bernard Chin Wee; Ong, Wei Jie; Shafie, Saleha; Abdin, Edimansyah; Poh, Porsche; Schomerus, Georg; Chong, Siow Ann; et al. (Frontiers in Public Health, 2025)
IntroductionKnowledge about the causes of mental illness is a crucial component of mental health literacy. Poor understanding of the etiology of mental illness can lead to stigmatizing behaviors and hinder access to appropriate help. The current cross-sectional study examined the general population’s causal beliefs about seven mental illnesses and explored the factor structure of the revised causal beliefs scale.MethodsFour thousand one hundred ninety-five respondents were randomly assigned a vignette and were asked questions on their recognition of the mental illness depicted, causal beliefs, and prior experience related to the mental illness (similar problems, had a mental health-related job or family and friends with similar problems). Exploratory and confirmatory factor analyses were used to examine the factor structure of the causal beliefs scale. Multivariable linear regression was used to examine its predictors.ResultsFactor analyses revealed a four-factor structure of causal beliefs: physical, psychosocial, personality, and biogenetic. Causal beliefs differed across the vignettes. Compared to schizophrenia, biogenetic beliefs were less likely to be endorsed for all mental illnesses except dementia, while personality beliefs were more likely to be endorsed for depression with suicidality. Compared to respondents who did not recognize the mental illness, those with correct recognition were more likely to endorse biogenetic and psychosocial beliefs, and less likely to endorse physical and personality beliefs.DiscussionFactor structure of the original causal beliefs scale was found to be valid in the Singapore population. Individuals who correctly recognized the mental illness appeared to comprehend its etiology well. However, some misconceptions about the etiology of mental illness persist, particularly with regards to relating obsessive-compulsive disorder to physical factors (e.g., virus) and depression with suicidality to personality flaws. As future awareness campaigns continue to address the gaps in literacy levels, careful promotion of certain causal beliefs is crucial to avoid conveying unintended messages.